Perbandingan Kinerja dan Kemudahan Implementasi Antara Configuration Management Ansible, Chef, dan Puppet - Auriza Rahmad Akbar; Jodhi Lesmana Putra (Departemen Ilmu Komputer, Institut Pertanian Bogor, 2021)
Installing computer lab software manually makes maintenance costly. Configuration management (CM) could simplify big and complex computer installation consistently and keep the system updated. This research compare the performance, syntax, and ease of implementation of some popular CM: Ansible, Chef, and Puppet. The test was done on a computer in local network using Vagrant with Virtualbox as provider. The test results on three VM client for lab software installation process showed that Chef needs the least time (30 minutes), followed closely by Ansible (31 minutes), and then Puppet (35 minutes). Chef syntax is the most likeable, whereas Ansible is easier to implement because it doesn’t need a server. From those results, we conclude that the right CM to be used in a computer lab scale is Ansible, because it is easier to implement with a good performance and support.